The effect of ice cream packaging design on consumer buying behavior / Nur Farahtul Akmar Mohamed Tharik - Mohamed Tharik, Nur Farahtul Akmar (Faculty of Art and Design, 2015)
When it comes to summer especially for Malaysia that having a hot weather, the first thing popping into people's mind is something cold like ice cream. Ice cream has become a common and popular ice product all these years and also it becomes a demand nowadays in all generation from kids to adults. Everyone knows ice cream. We can find a variety of ice cream in our market whether at supermarket, grocery stores, and even street vendors. When purchasing ice cream, we as a consumer may take many factors into considerations, such as brands, price, flavour and of course for our Muslims is a Halal logo. However, some consumers buy an ice cream based on what they are like or look that give attraction for them to buy it for example what they care may be the packaging design. The purpose of this research is to know the effect of ice cream packaging design to consumer buying behaviour by their packaging design. What element that appear on the packaging would affect customer to buy it and the finals I will know what kind of packaging design that our local consumer would prefer compare to local ice cream. This is because the element of colour, graphic and typography in packaging that give impact for consumer purchase decisions of food product. Colour is involved in almost every aspect of our daily life. The presence of colour becomes important in packaging design. The colour is some kind of visual attraction and impression that elicits emotion, creates mood and affects our behaviour. Consumers tended to first notice many products by the packaging colour. Customers will looking for a particular product on the shelf, packages with the same range of colour would attract their attention better than other.